113k views
5 votes
Step by step explanations for the following

g(x)=4x-5
f(x)= -2x-3
find (f•g) (-8)
and problems on the paper numbers 5-8 please ​

Step by step explanations for the following g(x)=4x-5 f(x)= -2x-3 find (f•g) (-8) and-example-1
User Lena Queen
by
5.1k points

1 Answer

3 votes

Answer:

5.
\bold{(g \circ f)(-3) = 16}}

6.
\bold{h(h(-3x)) = -12x + 15 }}

7.
{\bold{f\left(g\left(x-3\right)\right):\quad 3x-21}}

8.
\bold{\text \bold g(f(-3x)) = -36x + 15}}

Explanation:

These are examples of composite functions.

What is a composite function?
A function by definition is a process that takes a collection of inputs and produces a corresponding collection of outputs in such a way that the process produces one and only one output value for any single input value.

Since we consider a function a process it makes sense to think of two functions acting in sequence to produce a single output. The output from one function is fed into the second function.

  • A composite function can be written as:

    (f \circ g)(x)
  • The above can also be written as
    f(g(x)
  • This means the output of function
    g is fed as input to function
    f
  • We refer to g as the inner function and f as the outer function
  • The evaluation goes from inner to outer so first
    g(x) is evaluated and the result fed to
    f(x) as input which produces the composite result

Note that we can have
f
g as the outer function, in which case the notation will be
(g \circ f)(x) or
g(f(x))

Problem Solution

5.
g(x) = x + 3 \;\text and\; f(x) = 3x + 4
Find
(g \circ f)(-3) = g(f(-3))

  • First compute f(-3) in
    f(x) = 3x + 4
    ⇒ 3(3) + 4 = 9 + 4 = 13
  • Then use this value for
    x in
    g(x) = x + 3
    ⇒ 13 + 3 = 16

  • {\boxed{\bold{(g \circ f)(-3) = 16}}

6.
h(x) = 2x + 5
Find
h(h(-3x))

  • Here the output of h is fed into h again but the process of evaluation is the same
  • h(-3x) in h(x) = 2x + 5
    Substitute -3x wherever you see an x
    => 2 (-3x) + 5 => -6x + 5
  • Feed this into h again
    h((-3x)) = h(-6x + 5)
    = 2(-6x + 5) + 5
    = -12x +10 + 5
    = -12x + 15

  • \\\boxed{\bold{h(h(-3x)) = -12x + 15 }}


7.\;\;\;g\left(x\right)\:=\:x-\:3,\:f\left(x\right)\:=\:3x\:-\:3\\\\\text{Find } \:f\left(g\left(x-3\right)\right)


  • \mathrm{For}\:g=x-3\:\mathrm{substitute}\:x\:\mathrm{with}\:x-3

    =x-3-3 = x - 6

  • \mathrm{For}\:f=3x-3\:\mathrm{substitute}\:x\:\mathrm{with}\:x-6

    =3\left(x-6\right)-3
  • Simplify to get

    3x-21

  • \boxed{\bold{f\left(g\left(x-3\right)\right):\quad 3x-21}}

.
\bold{8.\;\;g(x) = 3x + 3, f(x) = 4x + 4}\\\\\bold{\text{Find } g(f(-3x))}


  • \text {For}\:f(x) =4x+4\:\mathrm{substitute}\:x\:\mathrm{with}\:-3x}

    =4\left(-3x\right)+4 =-12x+4

  • \mathrm{For}\:g=3x+3\:\mathrm{substitute}\:x\:\mathrm{with}\:-12x+4

    =3\left(-12x+4\right)+3 = -36x+12 + 3 = -36x + 15

  • \boxed{\bold{\text g(f(-3x)) = -36x + 15}}



User Mert Can Ilis
by
4.6k points